2021
DOI: 10.1101/2021.06.07.447263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome specific telomere lengths and the minimal functional telomere revealed by nanopore sequencing

Abstract: We developed a method to tag telomeres and measure telomere length by nanopore sequencing in the yeast S. cerevisiae. Nanopore allows long read sequencing through the telomere, subtelomere and into unique chromosomal sequence, enabling assignment of telomere length to a specific chromosome end. We observed chromosome end specific telomere lengths that were stable over 120 cell divisions. These stable chromosome specific telomere lengths may be explained by stochastic clonal variation or may represent a new bio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…14). The two same chromosome extremities were also described as the longest in W303, (Sholes et al ., 2021). The conservation of larger telomere size at TEL03L at the population level suggests that the underlying genetic determinants would be conserved since the species diverged from its last common ancestor at least ~180 KYA (see above).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14). The two same chromosome extremities were also described as the longest in W303, (Sholes et al ., 2021). The conservation of larger telomere size at TEL03L at the population level suggests that the underlying genetic determinants would be conserved since the species diverged from its last common ancestor at least ~180 KYA (see above).…”
Section: Resultsmentioning
confidence: 99%
“…This model implies that all individual telomeres would gradually converge toward the population mean length distribution after a sufficiently large number of divisions and that the overall telomere length distribution would converge to a steady state (Bianchi and Shore, 2008; Xu et al ., 2013). However, a recent study that used nanopore sequencing to measure individual telomere length reported that in W303, each chromosome end could have a specific and reproducible telomere length distribution that would remain stable over at least 120 generations (Sholes et al ., 2021). We examined telomere length variation between individual chromosome ends across the population of 100 strains.…”
Section: Resultsmentioning
confidence: 99%
“…Given the slow and progressive shortening of telomeres in adulthood, a highly sensitive method that can longitudinally detect telomere attrition in an individual in time is needed for both experimental and clinical studies 34 . In this regard, the recent development of long-read sequencing platforms has enabled the direct sequencing of telomere-containing genomic DNA fragments to obtain absolute telomere length at individual chromosome end [35][36][37][38][39] . However, current methods require the sequencing of whole genome to analyze the individual's telomere distribution, which precludes high-throughput capability.…”
mentioning
confidence: 99%
“…There is a clear need to better understand how TL measurement, using any assay, is impacted by polymorphic variation in subtelomeric regions and interstitial telomeric repeats. The use of direct sequencing via nanopore technology offers the unique possibility of generating a true "gold" standard TL measurement (25). Further, the completion of the sequencing of the human genome, telomere to telomere, is an opportunity to define the unique DNA sequences bridging the subtelomeric region and the telomere for each chromosome arm and leverage existing technologies such as STELA to determine the specific length of each unique chromosome (26).…”
Section: Discussionmentioning
confidence: 99%